Analisis Potensi Bahaya Penyebab Kecelakaan Pada Ruas Jalan Lingkar Utara Tegal – Brebes Dengan Metode HIRARC - Rofiul Izza Aulia; Meutya Jasmine; Suprapto Hadi (Jurnal Teknik Sipil, 2025)
Hazard Analysis of Accident Causes on the Brebes - Tegal North Ring Road Using the HIRARC Method. The Brebes-Tegal Northern Ring Road is a strategic route in the Pantura region with a high accident risk due to various factors. Using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method, this study analyzed potential hazards affecting road user safety. Field surveys and interviews revealed that the primary accident causes include road damage such as cracks, potholes, and elevation differences caused by heavy vehicle pressure. These risks are exacerbated by inadequate safety facilities, such as poor street lighting, damaged traffic signs, and the absence of side guards in high-risk areas. Illegal parking and disorganized vehicle entry-exit activities further increase the hazards. Improvement recommendations involve repairing road infrastructure, enhancing safety facilities, and enforcing strict regulations and traffic supervision. This study highlights the critical need for regular road safety inspections to identify and mitigate hazards, ensuring safer traffic conditions and supporting efficient mobility in the Pantura region.